Robinson Crusoe - Defoe, Daniel (Oxford University Press. London, 2020)
Robinson Crusoe is an adventure novel that tells the story of a young man, Robinson Crusoe, who defies his family$1 (Bs wishes and embarks on a life at sea. After a series of misfortunes, Crusoe is shipwrecked on a deserted island, where he spends 28 years in isolation. The novel explores his ingenuity and determination as he learns to survive by building shelter, growing food, and taming animals. Along the way, he grapples with loneliness, faith, and self-reliance. The novel emphasizes themes of survival, human resilience, and the ability to overcome adversity through resourcefulness.s